Transformative perspectives on labour geographies – The role of labour agency in processes of socioecological transformations. Issue 6 (2nd May 2021) - Grenzdörffer, Sinje Marlene
Abstract: Both geographical research on socioecological transformations and labour geography see decisive deficiencies in current capitalist structures centred around growth. To highlight possibilities of economic pluralism, both fields analyse diverse economic spaces within, next to and beyond capitalist structures. A basic assumption in transformation perspectives is that economic structures are not fixed, but can be transformed by people as economic actors. This corresponds to the concept of 'labour agency' from labour geography, i.e. that workers as active agents are able to (re)shape the structures they are embedded in. Despite those common perspectives, these threads of research coexist without having been intertwined. With a focus on wage labour, this paper addresses the potential for an integrative perspective illustrated by the example of companies owned/managed by workers. In charge of their own skills, time and resources, workers can actively break with prevalent market logics, which incentivise trading (human) resources at the lowest price possible. By rejecting core dynamics of capitalist structures, these companies illustrate the workers' potential key role in processes of socioecological transformations. Thus, the derived objectives of this paper are (1) to analyse and accentuate existing parallels between labour geography and research on socioecological transformations, (2) to illustrate the potential transformative impact of labour agency exemplified by companies in worker's hands and (3) to enrich the field of labour geography by an understanding of labour geographies as transformative spaces. This paper serves as a cornerstone and invitation for further research at this interface.